REWIEV OF SOME COMPOUND PERSONAL NAMES (Philological Studies, 2019)
The article’s author analyses the compound personal names: Berobran, Bregost, Dragoezd, Godoles, Ljudovid, Novosil, Pochest, Pretimir, Prvoslav, Velimazh, Verislav and Zhelovar, all of which have been confirmed in the onomastic fund pertaining to the Macedonian language areal. The analyzed personal names belong to the oldest anthroponimical layer of the Slavic languages and their analysis represents an extremely important contribution to the reconstruction of the Proto-Slavic antroponymy.
Keywords: personal name, antroponym, antroponymy, toponym, toponymy, Macedonian language